Aplicativo para implementação de rotas em plataforma de mapeamento web - Eugênio, Gabriel Fernando (2021)
Due to the popularity of smartphones, the use of apps as tools to aid in property management is increasingly present in the lives of farmers, with mapping and defining routes one of the most used functions in mobile device applications. In this work, an application for smartphones with the Android operating system was created using the Java programming language, which implements the Google Maps database through the use of the Application Programming Interface (API) Directions. The application has a map in its interface, where you can add two points and generate a route between them. This type of functionality is the basis for more complex projects, such as delivery management applications, vehicle fleet tracking, distance calculation, waste transport, among others. In an increasingly mobile world, it is essential to disseminate knowledge to farmers about the tools available, the necessary concepts and methods of implementing these mapping functions in applications in order to facilitate the understanding, development and access of these technologies to this audience.